Android Based Online Computer Technician Application - Mawa Faqu Rochman; Z I Rahmat (International Journal of Research and Applied Technology (INJURATECH), 2023)
This study aims to analyze the role of the Android-based Online Computer Technician. This study uses a quantitative description. An online Computer Technician application is to make it easier for customer actors to seek online computer technician services to repair damaged computers and provide convenience for users. The results of the study previously showed that computer users repairing computers by approaching technicians directly to offline stores and transforming into technicians approaching computer users' homes became a good solution. Using an Online Computer Technician Application can make it easier for computer users and not waste time, so they can optimize time properly and correctly.